UV Radiation Induced Cross-Linking of Whey Protein Isolate-Based Films - Markus Schmid; Tobias Konrad Prinz; Kerstin Müller; Andreas Haas (International Journal of Polymer Science)
Casted whey protein films exposed to ultraviolet irradiation were analyzed for their cross-linking properties and mechanical and barrier performance. Expected mechanical and barrier improvements are discussed with regard to quantification of the cross-linking in the UV-treated whey protein films. Swelling tests were used to determine the degree of swelling, degree of cross-linking, and cross-linking density. When the UV radiation dosage was raised, a significant increase of the tensile strength as well as an increase in Young’s modulus was observed. No significant changes in water vapor and oxygen barrier properties between the UV-treated films and an untreated reference sample could be observed. The cross-linking density and the degree of cross-linking significantly increased due to UV radiation. Combined results indicate a disordered protein network in cast films showing locally free volume and therefore only minor mechanical and barrier improvements.